Contestations and Resistance in the Sugarcane Economy in Mumias, Kenya - Peter Narh (Cadernos de Estudos Africanos)
The study is an examination of how agricultural intensification as a development paradigm gets entangled in farming processes of its adaptation and utilisation. Through qualitative research, it analyses the relationship around agricultural inputs and science for production of sugarcane, between farmers and Mumias Sugar Company Limited (Mumias Sugar) in western Kenya. The article demonstrates the potency of farmers’ resistance to aspects of intensification that stifle their control over the processes of sugarcane production and erode social and economic benefits they derive from sugarcane production. Strengthening the capacities of African farmers to adapt paradigms in ways that place their agroeconomies and benefits in their hands is thus emphasised.